Os batistas regulares e as armadilhas históricas do iluminismo - Silva, Francisco Jean Carlos da (2005)
Taking the Regular Baptist Churches of Rio Grande do Norte as the research field, this paper seeks to contribute to a new, more appropriate vision of the new picture of the religiosity of the Brazilian Protestantism. Established since 1938, the Regular Baptists Churches have been representing and producing their speech through their 58 churches spread throughout the state, besides a Theological School, two camps, an association (AIBRERN) and a House of Spiritual Assistance to Drug Dependents (CAEDD). A reflection of the symbolic substratum of the spirituality of the group agrees with the external description of its presence in RN. We understand that the Regular Baptists represent yet one more translation of a modern religious speech and that their focus is on the inheritance of a Christian fundamentalism based on the illuminist rationalism. In this way, we observed this group trying to find in its doctrines, practices and rules of conduct a demonstration that the spirit of the post-modernism challenges the group to new dynamics in the conservative model of its spirituality